Editorial: Urban Design – The Synthesis Discipline - Cuthbert, Alexander R. (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 6 No 1 (2019): April 2019DO - 10.24843/JRS.2019.v06.i01.p01, 2019)
-